Choreography for One, Two, and Three Legs (A phenomenological meditation in movements). Issue 2 (3rd July 2017) - Sobchack, Vivian
ABSTRACT: 'Choreography for One, Two, and Three Legs' approaches the intentional formation and performance of bodily movement and expression from the various perspectives of individuals who are 'differently abled'. Exploring what it is for a non-dancer to experience various rhythms, movements and spaces with crutches, prosthetic leg, and cane, the essay interweaves phenomenological description and interpretation of suddenly defamiliarized daily activities with discourse drawn from the experiences of professional dancers who are 'differently abled'. The aim is to foreground the opacities, transparencies, and ambiguities of a more general sense of embodied and expressive movement that subtends the 'abled' and 'differently abled' and the non-dancer and dancer. It is also to emphasize the lived – and living – body as the common ground that enables all of our thoughts, movements, and modes of expression, however differentiated their myriad forms.